Estudo da geometria atômica dos sistemas Au(110) e Au(110)-Sb. - Diogo Duarte dos Reis (2010)
In this work, we present the results of the atomic geometry determination of the clean Au(110)-(1x2) surface and with the adsorption of antimony by Low Energy Electron Diffraction (LEED). The Au(110)-(1x2) clean surface presents a reconstruction called missing row, which consists of an alternated removed atomic rows of the surface. In our LEED analysis, we found a large relaxation of the first layer, and a buckling in the third and fifth layers and also a pairing of atomic rows in the second and fourth layers, confforming the results found in the literature. For the system Au(110)-c(2x2)Sb we found that the surface rearranges in the structure (1x1) with antimony atoms occupying highly simetrical hollow sites, forming an overlayer over the Au(110)-(1x1) surface. These results dier from results of the literature, in which the Sb atoms occupy substitutionals sites in the rst layer forming a surface alloy. Our results are in very good agreement with recently performed ab initio calculations (DFT).